Implementation of differential wavefront sampling in optical alignment of pupil-segmented telescope systems - Lee, H; Dalton, G; Tosh, I; Kim, S (2008)
We describe the implementation of differential wavefront sampling(DWS) in optical alignment of a pupilsegmented telescope system. As a wavefront-based optical alignment method, DWS can efficiently provide estimations of misalignments present in an optical system by deliberately perturbing optical elements in a systematic manner. This has been demonstrated in our previous numerical studies with realistic uncertainties in wavefront measurements, motion control, and optical surface deformations, suggesting that the method has potential in optical alignment and phasing of pupil-segmented systems such as the future Extremely Large Telescopes (ELTs). The basic idea and procedures of DWS are first described. We then present and discuss preliminary simulations using the currently proposed European Extremely Large Telescope (E-ELT) as an example system.